Fungsi Directing Kepala Desa Dalam Pelaksanaan Program SDGs (Sustainable Development Goals) di Desa Tani Makmur Rengat Barat - Rina Rizki Amalia; Jehan Ridho Izharsyah (Universitas Muhammadiyah Sumatera Utara, 2022)
Sustainable Development or SDGS (Sustainable Development Goals) is a Global Development Agenda which has 17 Goals or objectives with the implementation not only focusing on human development but also environmentally friendly economic development and environmental development. The formulation of the problem in this research is how the directing function of the village head is in implementing the SDGS (Sustainable Development Goals) program in the Desa Tani Makmur Rengat Barat. The purpose of the study was to find out how the directing function of the village head was in implementing the SDGS (Sustainable Development Goals) program in the prosperous village of Rengat Barat. The type of research used in this study was a descriptive approach with qualitative analysis. The results of the research on the Implementation of the Sustainable Development Goals (SDGS) Program on proper sanitation were in accordance with what was planned in its implementation, which was in accordance with the predetermined distance. This can be seen from the obstacles that occur, for example the lack of education about clean water and proper sanitation where it is difficult to change people's habits in carrying out this program.